Environmental Effects on Yield and Quality in Three Sugarcane Varieties Grown in Veracruz, Mexico - Ramos, N. Milanês; Ruvalcaba, V. Enríquez; Caredo, M. Bello; Barahona, P. Ordóñez; Sarquís, Jorge I.; Solano, A. Herrera (International Journal of Bio-resource and Stress Management, 2010)
Two field trials were planted in October 2003 to evaluate the effect of time of harvest on performance by the three main sugarcane varieties in two contrasting locations within the largest sugarcane growing region in México. Trials were harvested at six timings during December 2004-May 2005 harvest season. In the dry zone, cane yield was highest early in the harvest season, i.e. December, through February, while yields declined from March onwards. In contrast, in the humid zone, the harvest season began with low cane yields in December and January, which reached a maximum in February and March, and declined during April and May. In CP 72-2086, reducing sugars showed low values early in the harvest season in the dry zone, which began to increase significantly in March and maintained high values until the end of the harvest season in May. Mex 69-290 recorded high values in December, decreasing in January, through March, and increasing again in April. Mex 79-431 maintained low values from December to March, which increased from April onwards. Main components analysis demonstrated significant effect by location on cane and sugar yields and time of harvest; influence of the environment on varietal yields and confirmed dependence of cane yield on stalk population, stalk length and diameter. Negative correlations between yield components and moisture, reducing sugars and fiber were also found.